Colonic carcinoid tumors: a clinicopathologic study of 23 patients from a single institution - Waisberg,Daniel Reis (2009)
CONTEXT: Colonic carcinoids, excluding those arising in the appendix, have proved to be extremely rare. Due to their rarity, the characteristics and behavior of this unusual malignancy remain unclear. OBJECTIVE: To review the clinicopathologic features of patients operated on carcinoid tumors of the colon. METHODS: Twenty-three patients (12 males and 11 females) were operated on colonic carcinoids. The mean age of the patients was 63.0 ± 12.9 years (42 to 85 years). The clinical and histopathological data of patients who were pathologically diagnosed as having carcinoid tumors and submitted to surgical treatment over a 30-year period (1977-2007) were gathered. Actuarial patient survival was estimated using the Kaplan-Meier method, with carcinoid-specific death as the outcome. RESULTS: The mean time elapsed between onset of symptoms and surgical treatment was 8.3 months (1.5 to 20 months). The most frequent symptoms or signs encountered were abdominal pain followed by anorexia or weight loss, diarrhea, abdominal tenderness, palpable abdominal mass, and rectal bleeding. No carcinoid syndrome was noted. The lesion was located in the cecum in 16 (69.6%) patients, in the sigmoid in 3 patients (13.0%), in the ascending colon in 3 patients (13.0%), and in the transverse colon in one patient (4.3%). Twenty-one (91.3%) patients were operated on curative intent. Spreading of the disease to the liver and peritoneum was found in two (8.7%) patients who submitted to intestinal bypass. The mean size of the largest mass was 3.7 ± 1.2 cm (1.5 to 6.2 cm). There were multiple (two or more) lesions in three cases (13.0%). In the resected cases, the lymph nodes were compromised in 10 patients (47.6%) and disease-free in 11 (52.4%). Venous invasion and neural infiltration were both present in five (23.8%) patients. The tumors had penetrated the muscularis propria in all resected cases. Four (17.4%) patients had a second non-carcinoid primary tumor. Three (13.0%) patients died due to postoperative complications and five (21.7%) patients died from metachronous metastases or local recurrence. Fifteen patients (65.2%) remain alive without evidence of active disease. The mean follow-up period was 12 years (1.2 to 18 years), whereas the mean global survival was 50.7 ± 34.2 months and the crude survival rate at 5 years was 62.7%. CONCLUSIONS: Carcinoid tumors of the colon are frequently right-sided and may be clinically occult until an advanced stage is reached. Based on the relatively poor survival rates reported, it is recommended that, in addition to standard surgical resection, vigorous surveillance for metastatic disease must be performed, particularly during the first 2 years after surgery. In addition, these patients require evaluation of the entire gastrointestinal tract for evidence of coexisting malignancy, along with an extended period of follow-up, because tumor recurrences after 5 years are not uncommon.